Red meat allergic patients have a selective IgE response to the α‐Gal glycan. Issue 11 (13th August 2015) - Apostolovic, D.; Tran, T. A. T.; Sánchez‐Vidaurre, S.; Cirkovic Velickovic, T.; Starkhammar, M.; Hamsten, C.; van Hage, M.
Abstract Galactose‐α‐1, 3‐galactose (α‐Gal) is a mammalian carbohydrate with significance in a novel type of food allergy. Patients with IgE against α‐Gal report severe allergic symptoms 3–6 h after consumption of red meat. We investigated whether IgE from red meat allergic patients recognizes other mammalian glycans than α‐Gal or glycans from the plant kingdom and insects of importance in allergy. We found that none of the 24 red meat allergic patients investigated had an IgE antibody response against the other abundant mammalian glycan N‐glycolylneuraminic acid or against cross‐reactive carbohydrate determinants from plant or venom sources (nCup a 1, nArt v 1, and MUXF3). Deglycosylation of an α‐Gal‐containing protein, bovine thyroglobulin, significantly reduced the IgE response. In conclusion, we show that red meat allergic patients have a selective IgE response to the α‐Gal glycan found in red meat. Other common glycans reactive in allergic disease are not targets of red meat allergic patients' IgE.